Seroprevalence of Borrelia burgdorferi among the indigenous people (Orang Asli) of Peninsular Malaysia - Khor, Chee-Sieng; Hassan, Habibi; Mohd-Rahim, Nurul-Farhana; Chandren, Josephine Rebecca; Nore, Siti-Sarah; Johari, Jefree; Loong, Shih-Keng; Abd-Jamil, Juraina; Khoo, Jing-Jing; Lee, Hai-Yen; Pike, Brian L; Li-Ping, Wong; et al. (Journal of infection in developing countries, 2019)
Introduction: Lyme disease has been well-described in the North America and European countries. However, information is still very limited in the developing countries including Malaysia. The Orang Asli (OA), the indigenous people of Peninsular Malaysia reside mostly in the forest and forest fringe areas abundant with the vector for Lyme disease. Here, we described the seroprevalence of Borellia burgdorferi (B. burgdorferi) among the OA and demographic variables that could be associated with seroprevalence. Methodology: A total of 16 OA villages distributed across 8 states in Peninsular Malaysia participated in this study. Sera obtained from 904 OA volunteers were screened for anti-B. burgdorferi IgG antibodies. ELISA results obtained and demographic information collected were analysed to identify possible variables associated with seroprevalence. Results: A total of 73 (8.1%) OA tested positive for anti-B. burgdorferi IgG antibodies. Among all the variables examined, village of residence (p = 0.045) was the only significant predictor for seropositivity. High (> 10.0%) prevalence was associated with three OA villages. Those living in one particular village were 1.65 times more likely to be seropositive as compared to other OA villages. Age, gender, marital status, household size, level of education, monthly household income and occupation were not significant predictors for seropositivity. Conclusion: Results of the present study support earlier findings that B. burgdorferi infection among Malaysians is currently under-recognized. Further studies will be needed at these locations to confirm the presence of Lyme disease among these populations.